2020
DOI: 10.3390/fi12020024
|View full text |Cite
|
Sign up to set email alerts
|

Well-Being and Social Media: A Systematic Review of Bergen Addiction Scales

Abstract: Does social media addiction impair the well-being of non-clinical individuals? Despite the Internet being able to be considered as a promoting factor for individual empowerment, previous literature suggests that the current massive availability of Information and Communication Technologies (ICT) may be dangerous for users’ well-being. This article discusses the relationship between the most used social media addiction measures (i.e., the Bergen Facebook Addiction Scale—BFAS, the Bergen Social Media Addiction S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 81 publications
5
64
0
2
Order By: Relevance
“…Moreover, the relation between the SNAddS-6S and the Short SNAddS-6S with life satisfaction was also congruent with the reviewed literature showing that Internet addiction and SNA are related to poorer levels of satisfaction with life [37,39,40,[42][43][44]. Accordingly, our results showed that the scores on the SNAddS-6S (or on the different factors) were higher, the more they were dissatisfied with life.…”
Section: The Snadds-6s a Multidimensional Valid And Reliable Scale supporting
confidence: 90%
“…Moreover, the relation between the SNAddS-6S and the Short SNAddS-6S with life satisfaction was also congruent with the reviewed literature showing that Internet addiction and SNA are related to poorer levels of satisfaction with life [37,39,40,[42][43][44]. Accordingly, our results showed that the scores on the SNAddS-6S (or on the different factors) were higher, the more they were dissatisfied with life.…”
Section: The Snadds-6s a Multidimensional Valid And Reliable Scale supporting
confidence: 90%
“…Therefore, it is of utmost importance to get access to real-world data from tech-companies such as Facebook to answer such questions [but see problems with the recently launched “Social Science One”-initiative; (Ledford, 2019 ; Hegelich, 2020 )]. Alternatively, when it is not possible to web-scrape data without intruding into user privacy, one could invest more research energy and funding into simulations of social media platforms, where different constellations of in-built features are tested for a variety of research questions targeting usage time, well-being (Brooks, 2015 ; Duradoni et al, 2020 ) and effects of filter-bubbles on radicalization (Zuiderveen Borgesius et al, 2016 ), among others. Additionally, it is crucial to combine information on digital footprints with self-report data in order to get deeper insights into how different groups of people are using social media (Montag and Elhai, 2019 ; Peterka-Bonetta et al, in press ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies indicate that excessive Internet use heightens the risk of substance use [28], and problematic gaming elevates the future risk of developing gambling problems. Addictive use of social media was reported to be related to reduced well-being [29]. These findings demand closer attention to whether PSU occurring during this critical developmental period leads to mental health problems later [30].…”
Section: Introductionmentioning
confidence: 97%